Effectiveness of Waste Management in Bitung City Environmental Agency - Audy G H Lengkong; Lexi Lumingkewas; Fitri H Mamonto (Universitas Muhammadiyah Gorontalo, 2021)
This study aims to analyze and describe the effectiveness of Waste Management at the Bitung City Environmental Service. The concept used is about the management of public services, the effectiveness of public services and excellent public services. The method used is qualitative, with a focus on the effectiveness of waste management through indicators of sorting, collecting, transporting and processing waste. Sources of data are leaders, structural officials in the field of waste management, supervisors and field officers and the community. The results showed that the waste had not been sorted and separated according to the type, time and place of disposing of the waste had not been complied with according to regulations, as well as the limited number and ability of collecting officers. Limited number and capacity of transportation means, working time or transportation cycle, not all waste has been processed and utilized through waste processing facilities. This study concludes: 1.) The collected waste has not been sorted and separated 2.) The collection of waste by field officers in all areas has not been maximized. 3.) Limited number of fleets, means of transportation, and working time and transportation cycles. 4.) Waste processing and utilization has not been maximized. There are several factors that affect the effectiveness of waste management at the Bitung City Environmental Service, including; Human resources, facilities and infrastructure, rules and regulations, limited land area for landfill.